2012
DOI: 10.1002/qua.24138
|View full text |Cite
|
Sign up to set email alerts
|

The first‐principles molecular dynamics study of quartz–water interface

Abstract: By first‐principles molecular dynamics, we have investigated the interaction of quartz (0001) surface with liquid water for two different fresh silica cleavages. The first type of cleavage is terminated by Si(O)2 and Si for two surfaces, respectively, whereas the second type cleavage has the same termination on both surfaces that consists of SiO. The water molecules were found to be decomposed and spontaneously form silanol group on both silica surfaces. After 4.0 ps, the chemical reactions were almost sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…from the ab initio MD simulations within the first 5 ps. It is expected that the reactive cleaved SiO 2 surface can be hydroxylated via hydrolysis reaction as reported by Ledyastuti et al 33 and Goumans et al 34 As shown in Figure 8 Figure 9 illustrates the detailed features regarding formation of HCO 3 configuration during hydrolysis reactions by using ELF. In Figure 9a, The charge transfer during the formation process of HCO 3 configuration on the basis of Bader analysis is shown in Figure 10.…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…from the ab initio MD simulations within the first 5 ps. It is expected that the reactive cleaved SiO 2 surface can be hydroxylated via hydrolysis reaction as reported by Ledyastuti et al 33 and Goumans et al 34 As shown in Figure 8 Figure 9 illustrates the detailed features regarding formation of HCO 3 configuration during hydrolysis reactions by using ELF. In Figure 9a, The charge transfer during the formation process of HCO 3 configuration on the basis of Bader analysis is shown in Figure 10.…”
Section: Resultsmentioning
confidence: 68%
“…In general, hydrolysis reaction occurs prior to carbonation reaction in the natural environment. However, according to previous works, 19,33 nonbridging O sites indeed can exist after hydrolysis reaction. In this paper, we studied carbonation at first.…”
mentioning
confidence: 70%
See 3 more Smart Citations